ANTIOXIDANT AND PROOXIDANT EFFECTS OF EPIGALLOCATECHIN GALLATE AND TANNIC ACID ON DNA DAMAGE IN HUMAN LYMPHOCYTES - Basaran, A.. A; Tokaç, D.; Aydin, S.; Basaran, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Dietary polyphenolic compounds are associated with a wide variety of beneficial health effects. The widely renowned biological actions of polyphenolic compounds are attributed to their antioxidant and free radical scavenging properties. They are however also reported to induce oxidative damage through the generation of reactive oxygen studies. Epigallocatechin gallate (EGCG) and tannic acid (TA) are abundant and active polyphenolic compounds mostly found in herbal teas, fruits and beverages. EGCG is the main constituent of catechin polyphenols found in green tea. It is suggested that EGCG can reduce the risk of certain types of diseases and cancers because of its antioxidant properties. TA is also used as a food additive. In the present study the modulating effects of EGCG and TA against the oxidative DNA damage induced by H2O2 in human lymphocytes were investigated by COMET assay. Briefly after incubating human lympocytes with ìl amounts of EGCG and TA at concentrations of 0.01-250 ìM, and 0.1-100 ìg/ml respectively with or without 0.05 ìm H2O2, DNA damage was determined. At the concentrations below 10 ìM of EGCG, and 100 ìg/ml of TA alone no significant DNA damage was observed. The concentrations above 10 ìM of EGCG alone seemed to induce DNA damage. However, at the concentrations of 0.01-30 ìM and 0.1-100 ìg/ml of EGCG and TA, respectively significantly reduced DNA strand breakage induced by 0.05 ìM H2O2 in human lymphocytes. In conclusion, it seems that our results highlight the potential benefit of EGCG and TA as natural antioxidants.